The impact of differentiated learning materials on students’ understanding of nationalism and global diversity - Ardiawan, I Ketut Ngurah; Lasmawan, I Wayan; Dantes, Nyoman; Dantes, Gede Rasben (Journal of Education and e-Learning Research, 2024)
This study aims to determine the differentiated learning materials’ impact on students’ understanding of nationalism and global diversity. This research was a quasi-experimental study conducted by following a post-test-only control group design. Two classes from different schools were selected as research samples using a statistical matching technique. The researchers collected the data using tests and analyzed them using descriptive statistics and an independent t-test to achieve the study’s objective. The results of the descriptive statistics showed that the experimental group had a higher score than the control group. It can be seen from the mean, minimum and maximum scores of the two groups. This result demonstrates that students who used varied learning resources had a greater comprehension of nationalism and global diversity. Furthermore, the independent t-test result confirmed that the differences in understanding were significant. In terms of the effect size, it confirms that differentiated instruction greatly affects students’ understanding of nationalism and global diversity. Thus, this study concluded that differentiated learning materials affect students’ understanding of nationalism and global diversity significantly. Thus, the researchers promote differentiated learning materials for teaching nationalism and global diversity based on the study results. Moreover, differentiated instruction may also be used for teaching different learning materials.